MiRNA- and cytokine-associated extracellular vesicles mediate squamous cell carcinomas. Issue 1 (1st January 2020) - Flemming, Joseph P.; Hill, Brianna L.; Haque, Mohammed W.; Raad, Jessica; Bonder, Claudine S.; Harshyne, Larry A.; Rodeck, Ulrich; Luginbuhl, Adam; Wahl, James K.; Tsai, Kenneth Y.; Wermuth, Peter J.; Overmiller, Andrew M.; et al.
ABSTRACT: Exosomes, or small extracellular vesicles (sEVs), serve as intercellular messengers with key roles in normal and pathological processes. Our previous work had demonstrated that Dsg2 expression in squamous cell carcinoma (SCC) cells enhanced both sEV secretion and loading of pro-mitogenic cargo. In this study, using wild-type Dsg2 and a mutant form that is unable to be palmitoylated (Dsg2cacs), we investigated the mechanism by which Dsg2 modulates SCC tumour development and progression through sEVs. We demonstrate that palmitoylation was required for Dsg2 to regulate sub-cellular localisation of lipid raft and endosomal proteins necessary for sEV biogenesis. Pharmacological inhibition of the endosomal pathway abrogated Dsg2-mediated sEV release. In murine xenograft models, Dsg2-expressing cells generated larger xenograft tumours as compared to cells expressing GFP or Dsg2cacs. Co-treatment with sEVs derived from Dsg2-over-expressing cells increased xenograft size. Cytokine profiling revealed, Dsg2 enhanced both soluble and sEV-associated IL-8 and miRNA profiling revealed, Dsg2 down-regulated both cellular and sEV-loaded miR-146a. miR-146a targets IRAK1, a serine-threonine kinase involved in IL-8 signalling. Treatment with a miR-146a inhibitor up-regulated both IRAK1 and IL-8 expression. RNAseq analysis of HNSCC tumours revealed a correlation between Dsg2 and IL-8. Finally, elevated IL-8 plasma levels were detected in a subset of HNSCC patients who did not respond to immune checkpoint therapy, suggesting that these patients may benefit from prior anti-IL-8 treatment. In summary, these results suggest that intercellular communication through cell-cell adhesion, cytokine release and secretion of EVs are coordinated, and critical for tumour growth and development, and may serve as potential prognostic markers to inform treatment options. Abbreviations: Basal cell carcinomas, BCC; Betacellulin, BTC; 2-bromopalmitate, 2-Bromo; Cluster of differentiation, CD; Cytochrome c oxidase IV, COX IV; Desmoglein 2, Dsg2; Early endosome antigen 1, EEA1; Epidermal growth factor receptor substrate 15, EPS15; Extracellular vesicle, EV; Flotillin 1, Flot1; Glyceraldehyde-3-phosphate dehydrogenase, GAPH; Green fluorescent protein, GFP; Head and neck squamous cell carcinoma, HNSCC; Interleukin-1 receptor-associated kinase 1, IRAK1; Interleukin 8, IL-8; Large EV, lEV; MicroRNA, miR; Palmitoylacyltransferase, PAT; Ras-related protein 7 Rab7; Small EV, sEV; Squamous cell carcinoma, SCC; Tissue inhibitor of metalloproteinases, TIMP; Tumour microenvironment, TME